Dissemination of Flood and Landslide Disaster Mitigation in Taman Baru Village, Sekotong, West Lombok - Mashadi, Usamah; Kurniawan, Wahyu; Suripto, Suripto (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Taman Baru Village, District of Sekotong, West Lombok Regency, with a population of around 4,234 people, has an area of ​​250 ha. The area has an average rainfall of 1381 mm with an average number of rainy days of 120 days. The village is located in a valley surrounded by hills with an altitude of 10 to 1000 meters above sea level. Thus, this village has a fairly high risk of flooding and landslides, especially during the rainy season. Based on the background of the problem above, it is necessary to conduct socialization of flood and landslide disaster mitigation in Taman Baru Sekotong Village, West Lombok. This community service activity was carried out with the aim of increasing community awareness, knowledge and skills regarding flood and landslide disaster mitigation in Taman Baru Village. The socialization activities were carried out using lecture, discussion, simulation and practice methods with assistance to the target audience, namely 20 people from 10 hamlets in Taman Baru Village. The results showed that 85% of participants were enthusiastic about following all stages of the socialization of flood and landslide disaster mitigation in Taman Baru Village. Participants' awareness and understanding of flood disaster mitigation increased, with material covering pre-flood mitigation, mitigation during floods, and post-flood mitigation, mapping and visualization of evacuation routes and assembly points. The outcomes of this activity were the availability of maps and visualizations of evacuation routes and assembly points in Taman Baru Village, Sekotong, West Lombok. This activity also has an impact on the availability of sufficient trash bins and in accordance with the types of waste sorted, as part of the flood and landslide disaster mitigation stages in the village.